Sovereignty : Frontiers of Possibility - Evans, Julie, 1952-; Genovese, Ann; Reilly, Alexander; Wolfe, Patrick, 1949- (Book collections on Project MUSE., 2013)
Unparalleled in its breadth and scope, 'Sovereignty' brings together some of the freshest and most original writing on sovereignty being done today. Sovereignty's many dimensions are approached from multiple perspectives and experiences. It is viewed globally as an international question; locally as an issue contested between Natives and settlers; and individually as survival in everyday life.